Functional silk fibroin drug carrier and preparation method thereof
By combining thioketal (TK) with silk fibroin (SF) to form ROS-responsive SF/TK nanoparticles, the problem of lack of targeting of drug carriers is solved, and high efficiency in inflammation and tumor treatment is achieved. The effect of targeted killing.
Patent Information
- Application Number
- CN202111170433.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-08
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-10-08
AI Technical Summary
Existing drug carriers lack precise targeting or localization, making it difficult to achieve efficient targeted killing in inflammation and tumor treatment.
By combining thioketal (TK) with carboxyl groups at both ends and silk fibroin (SF) to form ROS-responsive SF/TK nanoparticles, the C-S bond cleavage mechanism in ROS environment is used to achieve rapid drug release. .
Efficient drug release in tumor and inflammatory cells is achieved, significantly improving the accuracy and effectiveness of treatment while causing minimal damage to normal cells.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedicine, and in particular to a functional silk fibroin drug carrier and a preparation method thereof. Background Art
[0002] Cancer is one of the leading causes of death in the 21st century. Currently, chemotherapy is the mainstay of cancer treatment. However, chemotherapeutic drugs such as paclitaxel and doxorubicin lack specificity for tumor cells, indiscriminately killing both tumor cells and normal cells. Recently, ingenious drug delivery systems have been developed to effectively reduce toxic side effects by delivering drugs in a targeted manner. Nanoparticles, among others, have gained widespread application due to their small size, large surface area, high drug loading capacity, and ease of cellular endocytosis.
[0003] Compared with other natural and synthetic polymers, SF is a natural protein with good biocompatibility and biodegradability, is non-toxic and has no side effects. It is a biomaterial with broad application prospects. It has also received great attention in the research of drug carriers.
[0004] However, the clinical challenge facing drug carriers, including SF, is the lack of precise targeting or localization. Therefore, it is of great research value to endow SF drug carriers with intelligent response capabilities and improve the directionality and efficiency of drug carriers in the treatment of inflammation and tumors. Thioketal (TK) is a ROS-responsive compound that can be oxidized and broken in a ROS environment. ROS environments exist in most inflammatory tissues and tumor cells, so TK polymers have attracted attention for release and drug delivery therapy in inflammatory tissues and tumor cells.
[0005] Prior to the present invention, the responsive SF materials disclosed mainly included pH-responsive, magnetic-responsive, temperature-responsive, and light-responsive types. For example, a porous SF particle with folic acid grafted on the surface and loaded with doxorubicin showed pH-dependent drug release in vitro (Journal of Materials Science, 2019, 54(4): 3319). A magnetic SF nanoparticle loaded with doxorubicin can be used as a drug delivery system in multidrug-resistant cancer chemotherapy under magnetic field guidance (magnetic targeting) (Advanced Materials, 2014, 26: 7393). A multifunctional drug delivery microcarrier combining an SF inverse opal scaffold and a temperature-responsive poly(N-isopropylacrylamide) hydrogel can trigger drug release from the microcarrier by external temperature stimulation (Applied Materials Today, 2020, 19: UNSP 100540). A light-responsive carbon monoxide-releasing nanoparticle based on SF showed improved carbon monoxide release (Dalton Transactions, 2018, 47: 10434).
[0006] ROS-responsive materials primarily include sulfur, selenium, tellurium, and unsaturated lipid ROS-responsive carriers. An amphiphilic block copolymer containing a monoselenide, formed by the condensation polymerization of a dihydroxyalkyl selenide and a diisocyanate and terminated in polyethylene glycol monomethyl ether, undergoes structural decomposition and controlled release of the loaded drug in an oxidative environment (Polymer Chemistry, 2010, 1:1609). A tellurium polymer, in the presence of ultralow concentrations of hydrogen peroxide, rapidly swells and transforms into irregular aggregates, potentially serving as a combined chemotherapy and radiotherapy treatment (Chemical Communications, 2015, 51:7069). A near-infrared light-triggered liposome encapsulating a photosensitizer and tetrodotoxin provides on-demand, tunable local anesthesia (Proceedings of the National Academy of Sciences, 2015, 112:15719). Another example is a TK / polymer nanocarrier coated with the photosensitizer dihydrochlorin e6 and the chemotherapy drug doxorubicin, which can trigger the rapid release of the chemotherapy drug doxorubicin under 660nm red light irradiation (Chemistry of Materials, 2018, 30:517). Several intellectual property rights have been developed for the development of ROS-responsive drug-carrying nanomaterials, such as nanoparticles derived from vinylpyridine and polyethylene glycol via free radical polymerization, which can be used as a photosensitizer delivery vehicle (Application No. 201611126310.3); polycurcumin prodrug nanoparticles that can be used to load anticancer drugs and cyanine molecules (Application No. 201910191720.3); and a ROS-responsive amphiphilic material surface-modified with the selective antagonist AMD3100 and based on dextran and lipoic acid for the encapsulation and specific release of drugs for the treatment of liver fibrosis (Application No. 202010087783.7).
[0007] The present inventors have previously disclosed an exploratory study of a ROS-responsive SF drug delivery system, which showed a certain ROS-responsive effect but not significant. Therefore, it is very necessary to develop a ROS-efficient SF drug-loaded nanoparticle. Summary of the Invention
[0008] In view of this, the technical problem to be solved by the present invention is to provide a method for preparing a functional silk fibroin drug carrier. The functional silk fibroin drug carrier provided by the present invention improves the accuracy and effectiveness of drug treatment in diseased tissue sites; at the same time, it has significant ROS response performance.
[0009] The present invention provides a method for preparing a functional silk fibroin drug carrier, comprising:
[0010] A) degumming, dissolving, dialyzing, filtering, and concentrating silk from Bombyx mori to obtain a silk fibroin solution;
[0011] B) activating the thioketal with carboxyl groups at both ends with a cross-linking agent, and then mixing with the SF solution to react to obtain a reacted solution;
[0012] C) adding the reacted solution into a mixture of anhydrous ethanol and polyvinyl alcohol, stirring, freezing, thawing, centrifuging, and finally freeze-drying the precipitate to obtain the product.
[0013] Preferably, in step A), the degumming is performed using sodium carbonate or sodium bicarbonate; the dissolution is performed using lithium bromide; the molecular weight cutoff of the dialysis is 10 to 50 kDa; and the concentration of the silk fibroin solution is 10 to 200 mg / mL.
[0014] Preferably, the preparation method of the thioketal with carboxyl groups at both ends in step B) is as follows:
[0015] A mixture of 3-mercaptopropionic acid and anhydrous acetone reacts under acidic conditions, and the prepared crystals are washed, centrifuged, and freeze-dried to obtain TK with carboxyl groups at both ends;
[0016] The molar ratio of 3-mercaptopropionic acid to anhydrous acetone is 1:1.5-2.5; the acidic condition is hydrochloric acid; the concentration of the hydrochloric acid is 7-8 M; the reaction is specifically carried out at 20-30° C. for 4-8 hours; the freeze-drying is specifically carried out: pre-freezing at -20--80° C. for 2-6 hours and then freeze-drying for 8-16 hours.
[0017] Preferably, in step B), the mass ratio of the silk fibroin to the thioketal with carboxyl groups at both ends is 100:0.5-20; and the dissolving solvent of the thioketal with carboxyl groups at both ends is water.
[0018] Preferably, the cross-linking agent in step B) is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine; the amount of the cross-linking agent added is 2 to 2.5 times that of the thioketal with carboxyl groups at both ends;
[0019] The activation reaction temperature is 4-6°C;
[0020] The reaction temperature is 20-30° C.; the reaction time is 10-60 min.
[0021] Preferably, the concentration of the anhydrous ethanol in step C) is 0.5-1.5 M; the concentration of the polyvinyl alcohol is 5-60 mg / mL, and the molecular weight of the polyvinyl alcohol is 30,000-70,000;
[0022] The freezing is specifically: freezing at -20°C for 8 to 48 hours; the thawing is thawing at 20 to 30°C;
[0023] The centrifugation is performed at 13000 rpm;
[0024] The freeze-drying of the precipitate is specifically as follows: pre-freezing the precipitate at -20 to -80°C for 2 to 6 hours and then freeze-drying it for 8 to 16 hours.
[0025] The present invention provides a functional silk fibroin drug carrier, which is prepared by the preparation method described in any one of the above technical solutions.
[0026] The present invention provides the use of a functional silk fibroin drug carrier prepared by any one of the above-mentioned preparation methods in carrying anti-tumor / anti-inflammatory drugs.
[0027] The present invention provides a drug-loaded nanoparticle, comprising a drug and a functional silk fibroin drug carrier prepared by the preparation method described in any one of the above technical solutions.
[0028] Compared to existing technologies, the present invention provides a method for preparing a functional silk fibroin drug carrier, comprising: A) degumming, dissolving, dialyzing, filtering, and concentrating silk from Bombyx mori to obtain a silk fibroin solution; B) activating a thioketal with carboxyl groups at both ends with a crosslinker, followed by mixing and reacting with a SF solution to obtain a reacted solution; C) adding the reacted solution to a mixture of anhydrous ethanol and polyvinyl alcohol, stirring, freezing, thawing, centrifuging, and finally freeze-drying the precipitate. The SF / TK nanoparticles of the present invention incorporate a large amount of TK, a molecule that responds to ROS. The dual active functional carboxyl groups at the ends of TK covalently bond to the numerous hydroxyl groups on the SF molecular chain, bridging the gaps between SF molecules. In the treatment of tumors and inflammatory lesions, after being engulfed by tumor or inflammatory cells, the high intracellular oxygen concentrations cause the CS bonds of the TK molecules in the SF / TK nanoparticles to break, breaking the covalent bonds between the SF molecules. This in turn causes molecular cleavage within the nanoparticles, rapidly releasing the drug from the nanoparticles and targeting tumor and inflammatory cells. Meanwhile, upon entering normal cells, the nanoparticles undergo minimal or no cleavage, relying solely on osmotic release or release after degradation. Drug release is minimal and slow before being metabolized, resulting in minimal damage to normal cells. Furthermore, SF, a drug-loaded nanoparticle composed of 20 α-amino acids, which are identical to those found in the human body, is non-toxic and non-adverse, making it an ideal drug delivery vehicle. Through the use of manufacturing techniques, the crystalline structure of SF nanoparticles can be manipulated to control drug release through osmotic and degradation, thereby reducing the amount of drug released into normal cells before being metabolized and excreted. This makes it a suitable drug delivery vehicle for the targeted treatment of inflammation and tumors. DETAILED DESCRIPTION
[0029] The present invention provides a functional silk fibroin drug carrier and a method for preparing the same. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the desired effect. It should be noted that all similar substitutions and modifications are obvious to those skilled in the art and fall within the scope of protection of the present invention. The methods and applications of the present invention have been described through preferred embodiments. It is obvious that relevant personnel can modify or appropriately change and combine the methods and applications herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0030] The present invention provides a method for preparing a functional silk fibroin drug carrier, comprising:
[0031] A) degumming, dissolving, dialyzing, filtering, and concentrating silk from Bombyx mori to obtain a silk fibroin solution;
[0032] B) activating the thioketal with carboxyl groups at both ends with a cross-linking agent, and then mixing with the SF solution to react to obtain a reacted solution;
[0033] C) adding the reacted solution into a mixture of anhydrous ethanol and polyvinyl alcohol, stirring, freezing, thawing, centrifuging, and finally freeze-drying the precipitate to obtain the product.
[0034] The present invention provides a method for preparing a functional silk fibroin drug carrier. First, Bombyx mori silk is degummed.
[0035] The degumming process of the present invention is preferably carried out using sodium carbonate or sodium bicarbonate; more preferably, the degumming process is:
[0036] Weigh a certain amount of raw silk, take deionized water according to the bath ratio of 1:50 (w:v), add Na2CO3 or sodium bicarbonate to the cold water and stir evenly, add the raw silk for degumming after the water boils, take out and scrub, put it into the pot and boil again for degumming, repeat 2 to 3 times.
[0037] The degummed silk is placed in an electric constant temperature drying oven, dried, and pulled until fluffy to obtain degummed silk fibroin fibers. The present invention does not limit the specific drying temperature, which can be 50-70°C.
[0038] After degumming, dissolution is performed. The dissolution method of the present invention is preferably performed using lithium bromide. More preferably, a certain amount of degummed silk fibroin fibers is weighed, chopped, and placed in a lithium bromide solution, heated and stirred at 60-70°C for 1-2 hours to obtain a Bombyx mori SF dissolution solution. The concentration of lithium bromide is not limited in the present invention and is known to those skilled in the art, but is preferably 9-10 M.
[0039] After dissolution, the solution is dialyzed, filtered and concentrated to obtain a silk fibroin solution.
[0040] The silkworm SF solution is poured into a dialysis bag and placed in a container filled with deionized water for dialysis; the molecular weight cut-off of the dialysis of the present invention is 10-50 kDa, more preferably 25-50 kDa.
[0041] After dialysis, the product was filtered and concentrated by rotary evaporation in a fume hood.
[0042] The concentration of the silk fibroin solution of the present invention is preferably 10 to 200 mg / mL; more preferably 15 to 190 mg / mL; and most preferably 20 to 80 mg / mL.
[0043] The thioketal with carboxyl groups at both ends is activated with a cross-linking agent, and then mixed with the SF solution for reaction; the preparation method of the thioketal with carboxyl groups at both ends (TK with carboxyl groups at both ends) of the present invention is specifically as follows:
[0044] A mixture of 3-mercaptopropionic acid and anhydrous acetone reacts under acidic conditions, and the prepared crystals are washed, centrifuged, and freeze-dried to obtain TK with carboxyl groups at both ends;
[0045] 3-Mercaptopropionic acid and anhydrous acetone are mixed, preferably at a molar ratio of 1:1.5 to 2.5, more preferably 1:2 to 2.5, and reacted in hydrochloric acid at a concentration of 7 to 8 M. The reaction is carried out at 20 to 30°C for 4 to 8 hours, more preferably 22 to 28°C for 4 to 8 hours. The precipitated crystals are washed, centrifuged, and freeze-dried to obtain TK with carboxyl groups at both ends. The centrifugation is preferably at 13,000 rpm. The freeze-drying step is performed by pre-freezing at -20 to -80°C for 2 to 6 hours, followed by freeze-drying for 8 to 16 hours.
[0046] According to the present invention, the mass ratio of the silk fibroin to the thioketal with carboxyl groups at both ends is preferably 100:0.5-20; more preferably 100:1-10; and most preferably 100:1-8.
[0047] The solvent for dissolving the thioketal with carboxyl groups at both ends is water, and the solution is prepared at 0.1-0.5 mg / mL. Preferably, the solution can be placed in a 4° C. water bath and stirred for 20 minutes.
[0048] The activation reaction temperature of the present invention is 4-6°C;
[0049] The crosslinking agent of the present invention is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine; the amount of the crosslinking agent added is 2 to 2.5 times that of the ketal thiophenol with carboxyl groups at both ends;
[0050] The reaction temperature is preferably 20-30° C., more preferably 22-28° C.; the reaction time is preferably 10-60 min, more preferably 15-55 min.
[0051] The present invention preferably involves slowly adding a crosslinker to the TK solution, followed by reacting in a water bath at 4°C to 6°C for 10-15 minutes to activate the carboxyl groups. The activated TK is then slowly added to the SF solution, stirred slowly on a magnetic stirrer, and reacted at room temperature to produce the SF / TK composite solution.
[0052] The reaction solution is added into a mixed system of anhydrous ethanol and polyvinyl alcohol, stirred, frozen, thawed, centrifuged, and finally the precipitate is freeze-dried to obtain the product.
[0053] The concentration of the anhydrous ethanol of the present invention is preferably 0.5-1.5M; the concentration of the polyvinyl alcohol is preferably 5-60 mg / mL, more preferably 10-50 mg / mL, and the molecular weight of the polyvinyl alcohol is 30,000-70,000;
[0054] The freezing of the present invention is preferably: freezing at -20°C for 8 to 48 hours; more preferably freezing at -20°C for 10 to 48 hours;
[0055] The thawing is performed at 20°C to 30°C;
[0056] The centrifugation is performed at 13000 rpm;
[0057] The freeze-drying of the precipitate is specifically as follows: pre-freezing the precipitate at -20 to -80°C for 2 to 6 hours and then freeze-drying it for 8 to 16 hours.
[0058] The present invention provides a functional silk fibroin drug carrier, which is prepared by the preparation method described in any one of the above technical solutions.
[0059] The present invention has clearly described the above preparation method, which will not be repeated here.
[0060] The present invention provides the use of a functional silk fibroin drug carrier prepared by any one of the above-mentioned preparation methods in carrying anti-tumor / anti-inflammatory drugs.
[0061] Among them, anti-tumor / anti-inflammatory drugs include but are not limited to camptothecin.
[0062] The present invention provides a drug-loaded nanoparticle, comprising a drug and a functional silk fibroin drug carrier prepared by the preparation method described in any one of the above technical solutions.
[0063] When drugs are present, in the preparation of drug-loaded nanoparticles, the final step C) will become:
[0064] The anti-tumor drug camptothecin is added to the SF / TK composite solution under stirring, followed by a mixture of anhydrous ethanol and polyvinyl alcohol, stirred and mixed until uniform, and then frozen. The solution is dissolved, washed, and centrifuged at room temperature, and the precipitate at the bottom of the centrifuge tube is freeze-dried to obtain drug-loaded SF / TK nanoparticles. The concentration of the anhydrous ethanol in the present invention is preferably 0.5-1.5M; the concentration of the polyvinyl alcohol is preferably 5-60mg / mL, more preferably 10-50mg / mL, and the molecular weight of the polyvinyl alcohol is 30,000-70,000.
[0065] The present invention provides a method for preparing a functional silk fibroin drug carrier, comprising: A) degumming, dissolving, and dialysis-filtration-condensing silk from Bombyx mori silk to obtain a silk fibroin solution; B) activating a thioketal with carboxyl groups at both ends with a crosslinker, followed by mixing and reacting with a SF solution to obtain a reacted solution; C) adding the reacted solution to a mixture of anhydrous ethanol and polyvinyl alcohol, stirring, freezing, thawing, and centrifuging, and finally freeze-drying the precipitate. The SF / TK nanoparticles of the present invention incorporate a large amount of TK, a molecule that responds to ROS. The dual-functional carboxyl groups at the ends of TK covalently bond to the numerous hydroxyl groups on the SF molecular chain, bridging the gaps between SF molecules. In the treatment of tumors and inflammatory lesions, after being engulfed by tumor or inflammatory cells, the high intracellular oxygen concentrations cause the CS bonds of the TK molecules in the SF / TK nanoparticles to break, breaking the covalent bonds between the SF molecules. This in turn causes molecular cleavage within the nanoparticles, rapidly releasing the drug from the nanoparticles and targeting tumor and inflammatory cells. Meanwhile, upon entering normal cells, the nanoparticles undergo minimal or no cleavage, relying solely on osmotic release or release after degradation. Drug release is minimal and slow before being metabolized, resulting in minimal damage to normal cells. Furthermore, SF, a drug-loaded nanoparticle composed of 20 α-amino acids, which are identical to those found in the human body, is non-toxic and non-adverse, making it an ideal drug delivery vehicle. Through the use of manufacturing techniques, the crystalline structure of SF nanoparticles can be manipulated to control drug release through osmotic and degradation, thereby reducing the amount of drug released into normal cells before being metabolized and excreted. This makes it a suitable drug delivery vehicle for the targeted treatment of inflammation and tumors.
[0066] Furthermore, the SF molecule possesses amphiphilic and hydrophobic segments, possessing not only positively charged amino groups and negatively charged carboxyl groups but also a large number of hydroxyl groups for modification. This invention utilizes these hydroxyl groups, the most abundant functional group on the SF molecule, to prepare ROS-responsive, drug-loaded SF / TK nanoparticles. Based on the chemical structure of the SF molecule, it can be loaded with drugs with diverse surface properties. Therefore, the SF intelligent ROS-responsive drug delivery vehicle presented in this invention has great potential for treating a wide range of inflammatory and tumor diseases.
[0067] To further illustrate the present invention, a functional silk fibroin drug carrier and a preparation method thereof provided by the present invention are described in detail below with reference to examples.
[0068] Example 1
[0069] (1) Weigh a certain amount of raw silk and add deionized water at a bath ratio of 1:50 (w:v). Add Na2CO3 (0.06% by weight) to the cold water and stir evenly. After the water is boiled, add the raw silk for degumming. After 30 minutes, remove the silk and scrub it. Place it in a pot and boil it again for degumming. Repeat this process three times. Place the degummed silk in an electric constant temperature drying oven at 60°C and dry it until fluffy. This yields degummed silk fibroin fibers.
[0070] (2) Weigh a certain amount of degummed silk fibroin fibers, chop them into small pieces, and place them in a 9.3 M lithium bromide solution, heating and stirring at 65 ± 2°C for 1 hour to obtain a Bombyx mori SF solution. Pour the Bombyx mori SF solution into a dialysis bag and dialyze it against a container filled with deionized water to obtain a purified Bombyx mori SF aqueous solution. The concentration of the dialyzed SF aqueous solution was adjusted to 10-200 mg / mL.
[0071] (3) Weigh a certain amount of 3-mercaptopropionic acid and anhydrous acetone, add concentrated hydrochloric acid, and stir in a sealed container at room temperature for 6 hours. Place the mixed solution in an ice bath and rapidly cool it to quench the reaction until it turns into a white crystalline precipitate. Filter the crystals and wash them three times. Finally, centrifuge and wash, discard the supernatant, freeze the precipitate in a -80°C refrigerator for 4 hours, and then dry it in a freeze dryer for 12 hours to obtain TK with carboxyl groups at both ends that can be cleaved by ROS.
[0072] (4) The prepared TK was dissolved in deionized water to a concentration of 0.1-0.5 mg / mL. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine were slowly added dropwise to the TK solution at a molar ratio of 2-2.5 times that of TK. The mixture was then reacted in a 4°C water bath for 10 minutes to activate the carboxyl groups. The activated TK was slowly added dropwise to the SF aqueous solution at a mass ratio of SF:TK of 100:(1-5), stirred slowly on a magnetic stirrer, and reacted at room temperature for 1 hour to obtain an SF / TK composite solution.
[0073] (5) Add the anti-tumor drug camptothecin to the above SF / TK composite solution at a final concentration of 0.1-1 mg / mL under stirring, and then add anhydrous ethanol (V SF / TK :V 乙醇 =5:1), then add 2% polyvinyl alcohol solution, volume V 聚乙烯醇 =2(V SF / TK +V 乙醇), stirred and mixed thoroughly, and placed in a -20°C freezer for 48 hours before removal. Dissolved at room temperature, washed, and centrifuged, the precipitate at the bottom of the centrifuge tube was frozen at -80°C for 3 hours, and then freeze-dried for 12 hours to obtain drug-loaded SF / TK nanoparticles.
[0074] (6) The prepared camptothecin-loaded nanoparticles were rinsed and then tested for drug loading capacity. The absorbance of camptothecin at 365 nm was detected. The drug loading rate and encapsulation efficiency of the SF / TK drug-loaded nanoparticles were calculated to be 1.5-7.5% and 40-70%, respectively.
[0075] Example 2
[0076] (1) Weigh a certain amount of raw silk and add deionized water at a bath ratio of 1:50 (w:v). Add Na2CO3 (0.06% by weight) to the cold water and stir evenly. After the water is boiled, add the raw silk for degumming. After 30 minutes, remove the silk and scrub it. Place it in a pot and boil it again for degumming. Repeat this process three times. Place the degummed silk in an electric constant temperature drying oven at 60°C and dry it until fluffy. This yields degummed silk fibroin fibers.
[0077] (2) Weigh a certain amount of degummed silk fibroin fibers, chop them into small pieces, and place them in a 9.3 M lithium bromide solution, heating and stirring at 65 ± 2°C for 1 hour to obtain a Bombyx mori SF solution. Pour the Bombyx mori SF solution into a dialysis bag and dialyze it against a container filled with deionized water to obtain a purified Bombyx mori SF aqueous solution. The concentration of the dialyzed SF aqueous solution was adjusted to 10-200 mg / mL.
[0078] (3) Weigh a certain amount of 3-mercaptopropionic acid and anhydrous acetone, add concentrated hydrochloric acid, and stir in a sealed container at room temperature for 6 hours. Place the mixed solution in an ice bath and rapidly cool it to quench the reaction until it turns into a white crystalline precipitate. Filter the crystals and wash them three times. Finally, centrifuge and wash, discard the supernatant, freeze the precipitate in a -80°C refrigerator for 4 hours, and then dry it in a freeze dryer for 12 hours to obtain TK with carboxyl groups at both ends that can be cleaved by ROS.
[0079] (4) The prepared TK was dissolved in deionized water to a concentration of 0.1-0.5 mg / mL. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine were slowly added dropwise to the TK solution at a molar ratio of 2-2.5 times that of TK. The mixture was then reacted in a 4°C water bath for 10 minutes to activate the carboxyl groups. The activated TK was slowly added dropwise to the SF aqueous solution at a mass ratio of SF:TK of 100:3. The mixture was stirred slowly on a magnetic stirrer and reacted at room temperature for 1 hour to obtain an SF / TK composite solution.
[0080] (5) Add the anti-tumor drug camptothecin to the above SF / TK composite solution at a final concentration of 0.5 mg / mL under stirring, and then add anhydrous ethanol (V SF / TK :V 乙醇 =5:1), then add 2% polyvinyl alcohol solution, volume V 聚乙烯醇 =2(V SF / TK +V 乙醇 ), stirred and mixed thoroughly, and placed in a -20°C freezer for 48 hours before removal. Dissolved at room temperature, washed, and centrifuged, the precipitate at the bottom of the centrifuge tube was frozen at -80°C for 3 hours, and then freeze-dried for 12 hours to obtain drug-loaded SF / TK nanoparticles.
[0081] (6) The prepared SF / TK nanoparticles loaded with camptothecin were rinsed and then the particle size was tested before and after oxygen cleavage. The particle size of the SF / TK drug-loaded nanoparticles decreased with the increase of the treatment time with 50mM KO2 solution. After 16 hours of treatment, the particle size decreased from the initial 426nm to 257nm. That is, the TK in the SF / TK nanoparticles encountered an oxygen environment, the chemical bonds were broken and released, and the nanoparticles were destroyed from the inside. After being freeze-dried again, they shrank severely and cleaved, causing the nanoparticles to break. This shows that the SF / TK drug-loaded nanoparticles can be cleaved in an oxygen environment.
[0082] (7) The drug release behavior of the prepared SF / TK nanoparticles loaded with camptothecin was observed in an oxygen-treated environment. In an oxygen environment, the SF / TK nanoparticles released the drug quickly, especially in the first 12 hours, and then the release slowed down. After 8 hours of oxygen treatment, the cumulative drug release rate of the SF / TK nanoparticles reached about 47%. After 48 hours, the cumulative drug release rate of the SF / TK nanoparticles was about 72%, which was significantly higher than the release rate of the control. The drug release amount of the SF / TK nanoparticles in a non-oxygen environment for 48 hours was much less than that in an oxygen environment. That is, the SF / TK nanoparticles broke in an oxygen environment due to TK response, allowing the SF / TK nanoparticles to release the drug quickly, and have significant ROS response performance.
[0083] Example 3
[0084] (1) Weigh a certain amount of raw silk and add deionized water at a bath ratio of 1:50 (w:v). Add Na2CO3 (0.06% by weight) to the cold water and stir evenly. After the water is boiled, add the raw silk for degumming. After 30 minutes, remove the silk and scrub it. Place it in a pot and boil it again for degumming. Repeat this process three times. Place the degummed silk in an electric constant temperature drying oven at 60°C and dry it until fluffy. This yields degummed silk fibroin fibers.
[0085] (2) Weigh a certain amount of degummed silk fibroin fibers, chop them into small pieces, and place them in a 9.3 M lithium bromide solution, heating and stirring at 65 ± 2°C for 1 hour to obtain a Bombyx mori SF solution. Pour the Bombyx mori SF solution into a dialysis bag and dialyze it against a container filled with deionized water to obtain a purified Bombyx mori SF aqueous solution. The concentration of the dialyzed SF aqueous solution was adjusted to 10-200 mg / mL.
[0086] (3) Weigh a certain amount of 3-mercaptopropionic acid and anhydrous acetone, add concentrated hydrochloric acid, and stir in a sealed container at room temperature for 6 hours. Place the mixed solution in an ice bath and rapidly cool it to quench the reaction until it turns into a white crystalline precipitate. Filter the crystals and wash them three times. Finally, centrifuge and wash, discard the supernatant, freeze the precipitate in a -80°C refrigerator for 4 hours, and then dry it in a freeze dryer for 12 hours to obtain TK with carboxyl groups at both ends that can be cleaved by ROS.
[0087] (4) The prepared TK was dissolved in deionized water to a concentration of 0.1-0.5 mg / mL. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine were slowly added dropwise to the TK solution at a molar ratio of 2-2.5 times that of TK. The mixture was then reacted in a 4°C water bath for 10 minutes to activate the carboxyl groups. The activated TK was slowly added dropwise to the SF aqueous solution at a mass ratio of SF:TK of 100:5. The mixture was stirred slowly on a magnetic stirrer and reacted at room temperature for 1 hour to obtain an SF / TK composite solution.
[0088] (5) Add the anti-tumor drug camptothecin to the above SF / TK composite solution at a final concentration of 0.5 mg / mL under stirring, and then add anhydrous ethanol (V SF / TK :V 乙醇 =5:1), then add 2% polyvinyl alcohol solution, volume V 聚乙烯醇 =2(V SF / TK +V 乙醇 ), stirred and mixed thoroughly, and placed in a -20°C freezer for 48 hours before removal. Dissolved at room temperature, washed, and centrifuged, the precipitate at the bottom of the centrifuge tube was frozen at -80°C for 3 hours, and then freeze-dried for 12 hours to obtain drug-loaded SF / TK nanoparticles.
[0089] (6) The prepared SF / TK nanoparticles loaded with camptothecin were rinsed and then the particle size was tested before and after oxygen cleavage. The particle size of the SF / TK drug-loaded nanoparticles decreased with the increase of the treatment time with 50mM KO2 solution. After 16 hours of treatment, the particle size decreased from the initial 532nm to 315nm. That is, the TK in the SF / TK nanoparticles encountered an oxygen environment, the chemical bonds were broken and released, and the nanoparticles were destroyed from the inside. After being freeze-dried again, they shrank severely and cleaved, resulting in the breakage of the nanoparticles. This shows that the SF / TK drug-loaded nanoparticles can be cleaved in an oxygen environment.
[0090] (7) The drug release behavior of the prepared SF / TK nanoparticles loaded with camptothecin was observed in an oxygen-treated environment. In an oxygen environment, the SF / TK nanoparticles released the drug quickly, especially in the first 12 hours, and then the release slowed down. After 8 hours of oxygen treatment, the cumulative drug release rate of the SF / TK nanoparticles reached about 59%. After 48 hours, the cumulative drug release rate of the SF / TK nanoparticles was about 81%, which was significantly higher than the release rate of the control. The drug release amount of the SF / TK nanoparticles in a non-oxygen environment for 48 hours was much less than that in an oxygen environment. That is, the SF / TK nanoparticles broke in an oxygen environment due to TK response, allowing the SF / TK nanoparticles to release the drug quickly, and have significant ROS response performance.
[0091] Comparative Example 1
[0092] (1) Weigh a certain amount of raw silk and add deionized water at a bath ratio of 1:50 (w:v). Add Na2CO3 (0.06% by weight) to the cold water and stir evenly. After the water is boiled, add the raw silk for degumming. After 30 minutes, remove the silk and scrub it. Place it in a pot and boil it again for degumming. Repeat this process three times. Place the degummed silk in an electric constant temperature drying oven at 60°C and dry it until fluffy. This yields degummed silk fibroin fibers.
[0093] (2) Weigh a certain amount of degummed silk fibroin fibers, chop them into small pieces, and place them in a 9.3 M lithium bromide solution, heating and stirring at 65 ± 2°C for 1 hour to obtain a Bombyx mori SF solution. Pour the Bombyx mori SF solution into a dialysis bag and dialyze it against a container filled with deionized water to obtain a purified Bombyx mori SF aqueous solution. The concentration of the dialyzed SF aqueous solution was adjusted to 10-200 mg / mL.
[0094] (3) 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine were added to the SF aqueous solution in the same proportion as in the above example, and then reacted in a 4°C water bath for 10 minutes, and then stirred at room temperature for 1 hour. The anti-tumor drug camptothecin was added to the above SF reaction solution at a final concentration of 0.5 mg / mL, and then anhydrous ethanol (V SF :V 乙醇 =5:1), then add 2% polyvinyl alcohol solution, volume V 聚乙烯醇 =2(V SF +V 乙醇 ), stirred and mixed evenly, placed in a -20°C freezer for 48 hours, and then removed. Dissolved at room temperature, washed, and centrifuged, the precipitate at the bottom of the centrifuge tube was frozen at -80°C for 3 hours, and then freeze-dried for 12 hours to obtain drug-loaded SF nanoparticles.
[0095] (4) The drug loading capacity of the prepared pure SF nanoparticles loaded with camptothecin was comparable to that of SF / TK nanoparticles. The prepared SF nanoparticles loaded with camptothecin were rinsed and then subjected to particle size tests before and after oxygen cleavage. The particle size of the SF drug-loaded nanoparticles increased first and then slightly decreased with increasing treatment time with 50 mM KO2 solution. The initial average particle size of the SF drug-loaded nanoparticles was 325 nm. As the oxygen treatment time increased to 2 hours, the particle size of the SF drug-loaded nanoparticles increased to 400 nm due to water absorption and swelling. After 16 hours of oxygen treatment, the particle size decreased to 370 nm, which was still larger than the particle size of the original particles, indicating that the SF drug-loaded nanoparticles did not undergo significant cleavage.
[0096] (5) The prepared camptothecin-loaded SF nanoparticles were subjected to oxygen-treated conditions to observe their drug release behavior. In oxygen-treated conditions, the SF drug-loaded nanoparticles released the drug slowly, with the cumulative drug release rate of the SF drug-loaded nanoparticles less than 40% after 48 hours. The drug release of the SF drug-loaded nanoparticles in a non-oxygen environment over 48 hours was close to that in oxygen, indicating that pure SF drug-loaded nanoparticles did not exhibit significant ROS response.
[0097] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a functional silk fibroin drug carrier, characterized in that: include: A) degumming, dissolving, dialyzing, filtering and concentrating silk from Bombyx mori to obtain a silk fibroin solution; B) activating the thioketal with carboxyl groups at both ends with a crosslinking agent, and then mixing with a SF solution to react, to obtain a solution after the reaction; the crosslinking agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine; the amount of the crosslinking agent added is 2 to 2.5 times the molar ratio of the thioketal with carboxyl groups at both ends; the mass ratio of the silk fibroin to the thioketal with carboxyl groups at both ends is 100:5; the preparation method of the thioketal with carboxyl groups at both ends is specifically as follows: a mixture of 3-mercaptopropionic acid and anhydrous acetone is reacted under acidic conditions, and the prepared crystals are washed, centrifuged, and freeze-dried to obtain TK with carboxyl groups at both ends; C) adding the solution after the reaction into a mixed system of anhydrous ethanol and polyvinyl alcohol, stirring, freezing, thawing, centrifuging, and finally freeze-drying the precipitate to obtain the product.
2. The preparation method according to claim 1, characterized in that: Step A) The degumming is performed by using sodium carbonate or sodium bicarbonate; the dissolution is performed by using lithium bromide; the molecular weight cutoff of the dialysis is 10-50 kDa; and the concentration of the silk fibroin solution is 10-200 mg / mL.
3. The preparation method according to claim 1, characterized in that: Step B) The molar ratio of 3-mercaptopropionic acid to anhydrous acetone is 1:1.5-2.5; the acidic condition is hydrochloric acid; the concentration of hydrochloric acid is 7-8M; the reaction is specifically carried out at 20-30°C for 4-8 hours; the freeze-drying is specifically carried out: pre-freezing at -20--80°C for 2-6 hours and then freeze-drying for 8-16 hours.
4. The preparation method according to claim 1, characterized in that: In step B), the solvent for dissolving the thioketal with carboxyl groups at both ends is water.
5. The preparation method according to claim 1, characterized in that: Step B) the activation reaction temperature is 4-6°C; The reaction temperature is 20-30° C., and the reaction time is 10-60 min.
6. The preparation method according to claim 1, characterized in that: Step C) the concentration of the anhydrous ethanol is 0.5-1.5M; the concentration of the polyvinyl alcohol is 5-60mg / mL, and the molecular weight of the polyvinyl alcohol is 30,000-70,000; The freezing is specifically: freezing at -20°C for 8 to 48 hours; the thawing is thawing at 20 to 30°C; The centrifugation is performed at 13000 rpm; The freeze drying of the precipitate is specifically as follows: pre-freezing the precipitate at -20 to -80°C for 2 to 6 hours and then freeze-drying it for 8 to 16 hours.
7. A functional silk fibroin drug carrier, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the functional silk fibroin drug carrier prepared by the preparation method according to any one of claims 1 to 6 in the preparation of anti-tumor / anti-inflammatory drug carriers.
9. A drug-loaded nanoparticle comprising a drug and a functional silk fibroin drug carrier prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Active oxygen stimuli-responsive nanogel drug barrier and preparation method and application thereof
CN108610460A
Preparation and application of a highly drug-loaded polycurcumin prodrug nanocarrier with reactive oxygen species responsiveness
CN110051855B
Active oxygen response type drug carrier targeting hepatic stellate cells
CN111249474A